2022
DOI: 10.3389/fmicb.2022.946995
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota and C-Type Lectin Receptors in Cancers: Know thy Neighbors

Abstract: Numerous studies have demonstrated the importance of gut bacteria in the development of malignancy, while relatively little research has been done on gut mycobiota. As a part of the gut microbiome, the percentage of gut mycobiota is negligible compared to gut bacteria. However, the effect of gut fungi on human health and disease is significant. This review systematically summarizes the research progress on mycobiota, especially gut fungi, in patients with head and neck cancer (HNC), esophageal cancer (EC), gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 168 publications
(278 reference statements)
0
7
1
Order By: Relevance
“…However, contrary to our expectation, we found both cell lines expressed comparable amounts of dectin-2 protein (12). A recent study suggested that dectin-1, another C-type lectin receptor (14), has a role distinct from that of dectin-2 in skin wound-healing through its different effects on neutrophilic inflammatory response (18). Therefore, in order to clarify the possible role of dectin-1 in UVC sensitivity, dectin-1 protein expression was compared in UVC-sensitive and -resistant cells.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…However, contrary to our expectation, we found both cell lines expressed comparable amounts of dectin-2 protein (12). A recent study suggested that dectin-1, another C-type lectin receptor (14), has a role distinct from that of dectin-2 in skin wound-healing through its different effects on neutrophilic inflammatory response (18). Therefore, in order to clarify the possible role of dectin-1 in UVC sensitivity, dectin-1 protein expression was compared in UVC-sensitive and -resistant cells.…”
contrasting
confidence: 99%
“…We reported the prominent anti-UVC activity of lignincarbohydrate complex (LCC) (13). LCC from Lentinus edodes mycelia extract enhanced gene expression of dectin-2, a C-type lectin receptor (14) which recognizes microbial polysaccharides (15). This suggests a significant role of the activation of the dectin-2 signaling pathway as a result of LCC action.…”
mentioning
confidence: 99%
“…Aflatoxins (mycotoxins produced by secondary metabolism of the fungus Aspergillus flavus and Aspergillus parasiticus ) are known to induce HCC [ 17 ]. In addition to the carcinogenic role of mycotoxins, several studies have shown that the intestinal mycobiota is directly involved in the development of colorectal, oral, and pancreatic cancer [ 18 – 26 ], and multicentre clinical research has revealed that gut fungi can be used for the diagnosis of colorectal cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Aykut et al made the groundbreaking discovery that fungi could move from the intestinal lumen to the pancreas and that pathogenic fungi stimulate pancreatic adenocarcinoma via activating the mannosebinding lectin/complement-3 pathway (Aykut et al, 2019). Our previous review also detailed the close relationship between intestinal fungi and cancers of the colorectum, cavity, stomach, esophagus, and pancreas (Zhang et al, 2022). Thus, it is necessary to perform further studies regarding the changes in the composition of fecal fungi in the progression from health to ICC, thereby providing a new theoretical basis for the prevention and treatment of ICC.…”
Section: Introductionmentioning
confidence: 99%